Media Matters : Race and Gender in U.S. Politics. - Fiske, John (University of Minnesota Press, 1994)
Illustrates how people engaged in struggles over race, class and gender have influenced the way the nation made sense of key media events such as the O.J. Simpson murder trial, the Anita Hill-Clarence Thomas hearings, the L.A. riots, and the family values debate between Dan Quayle and Murphy Brown.